LINGUISTIC TERMINOLOGY AS AN OBJECT OF RESEARCH IN UKRAINIAN TERMINOLOGY - KIM, Su Hyun (Linguistic and Conceptual Worldviews, 2022)
In Ukrainian linguistics, there have been various studies of special relationships to the individual subdivisions of linguistic terminology; the internal and inter-systemic semantic connections of terms, their special relations to commonly used forms, the formation and historical development of linguistic terminology, their origin and function, and the organization of systematic structures. More particularly, in the late 20th century, the study of various structural-semantic and functional features that appear in the study of Ukrainian terminology was intensified. Therefore, terminology will refer to the actual areas of linguistics, especially historical terminology.This article will provide an overview of the linguistic works of several Ukrainian scholars, including V. V. Derkach, O. A. Katsimon, N. A. Lyashuk, O. V. Medved, N. A. Moskalenko, L. V. Rohach, L. V. Turovska, H. M. Tsyhanok, Yu. A. Chernobrov, V. Y. Chykut, D. B. Yakymovych-Chapran, I. A. Yaroshevych, V. V. Zakharchyn, I. I. Ohiyenko, S. M. Polyuha, whose works consider the linguistic terminology from the 20th to the beginning of the 21 th century. The object is to give a dissertation of scientists of the 20th to the beginning of the 21th century and to analyze the subjects and the methods of these scholars' works. This study looks at the impact of the work of these scholars and highlights their influence on the development of Ukrainian linguistics over the years. This is done through a categorization of the linguistic systems that these many of these scholars took interest in, as well as those that they did not, but may have overlooked.Some more detailed classification criteria are presented, including phonetical, grammatical, morphological, and syntactic terminological vocabularies and groups of terminologies that are used in the writings of specific scholars or in specific territories. This allows us to observe the development of Ukrainian terminology from various angles.
Keywords: linguistic terminology, Ukrainian linguistics, terminology, terms-systems, term, Ukrainian, History of Ukrainian language